1975
DOI: 10.1007/bf01315594
|View full text |Cite
|
Sign up to set email alerts
|

Serologic evidence for etiologic role of Akabane virus in epizootic abortion-arthrogryposis-hydranencephaly in cattle in Japan, 1972?1974

Abstract: In the outbreak of abortions, premature births, stillbirths and congenital arthrogryposis-hydranencephaly (AH) syndrome in Japan during the summer through winter of 1972-73 and 1973-74, precolostral sera from calves with congenital AH syndrome and normal calves were tested for neutralizing antibodies against some arboviruses, i.e. Akabane, Aino, Getah and Japanese encephalitis (JE) viruses. The incidence of antibody for Akabane virus was very high in calves with AH syndrome (49/59 or 83 per cent) as compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 17 publications
1
73
0
1
Order By: Relevance
“…Another virus strain related to Akabane was isolated from culicoides midges in South Africa (Theodoridis et al 1979). Akabane virus has been shown to be the cause of abortions and a congenital arthrogryposis hydranencephaly syndrome in cattle and sheep in Japan, Australia and Israel (Kurogi et al 1975;Markusfeld & Mayer, 1971;Hartley et al 1975). This syndrome has not been described in Africa other than as a consequence of the vaccination of sheep with an attenuated Rift Valley fever vaccine (F. G. Davies, unpublished data;Coetzer & Barnard, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Another virus strain related to Akabane was isolated from culicoides midges in South Africa (Theodoridis et al 1979). Akabane virus has been shown to be the cause of abortions and a congenital arthrogryposis hydranencephaly syndrome in cattle and sheep in Japan, Australia and Israel (Kurogi et al 1975;Markusfeld & Mayer, 1971;Hartley et al 1975). This syndrome has not been described in Africa other than as a consequence of the vaccination of sheep with an attenuated Rift Valley fever vaccine (F. G. Davies, unpublished data;Coetzer & Barnard, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Akabane virus was strongly suggested to be the etiologic agent of epizootic abortion and congenital AH syndrome in cattle (Miura et al, 1974;Kurogi et al ., 1975). Incidence of antibody to Akabane virus in normal calves and cows is not different from our data on Aino virus.…”
Section: Prefecturementioning
confidence: 99%
“…Miura et al (1974) and Kurogi et al (1975) studied the incidence of neutralizing antibody to Aino virus in calves and cows with congenital arthrogryposis-hydranencephaly (AH) syndrome and reported that 2 of 20 (Miura et al, 1978) and 2 of 52 (Kurogi et al, 1975) calves had antibody to the virus.…”
Section: Prefecturementioning
confidence: 99%
“…AKA virus has been shown to cause abnormal deliveries, such as abortion, stillbirth, premature birth and deformities among cattle, sheep and goats [8,16]. The epizootics of congenital arthrogryposis-hydranencephaly (AH) syndrome caused by AKA virus were observed in 1972-1974 [11,12]. Although the decennial occurrences of AH syndrome had been reported in Japan until a vaccine was developed, sporadic outbreaks of the disease have been observed in the southern part of Japan at the present time.…”
mentioning
confidence: 99%